Involvement of the TCR Cβ FG Loop in Thymic Selection and T Cell Function - Sasada, Tetsuro (The Rockefeller University Press, 2002)
The asymmetric disposition of T cell receptor (TCR) Cβ and Cα ectodomains creates a cavity with a side-wall formed by the rigid Cβ FG loop. To investigate the significance of this conserved structure, we generated loop deletion (βΔFG) and βwt transgenic (tg) mice using the TCR β subunit of the N15 CTL. N15βwt and N15βΔFG H-2(b) animals have comparable numbers of thymocytes in S phase and manifest developmental progression through the CD4(−)CD8(−) double-negative (DN) compartment. N15βΔFG facilitates transition from DN to CD4(+)8(+) double-positive (DP) thymocytes in recombinase activating gene (RAG)-2(−/−) mice, showing that pre-TCR function remains. N15βΔFG animals possess ∼twofold more CD8(+) single-positive (SP) thymocytes and lymph node T cells, consistent with enhanced positive selection. As an altered Vα repertoire observed in N15βΔFG mice may confound the deletion's effect, we crossed N15αβ TCR tg RAG-2(−/−) with N15βΔFG tg RAG-2(−/−) H-2(b) mice to generate N15αβ RAG-2(−/−) and N15αβ.βΔFG RAG-2(−/−) littermates. N15αβ.βΔFG RAG-2(−/−) mice show an 8–10-fold increase in DP thymocytes due to reduced negative selection, as evidenced by diminished constitutive and cognate peptide-induced apoptosis. Compared with N15αβ, N15αβ.βΔFG T cells respond poorly to cognate antigens and weak agonists. Thus, the Cβ FG loop facilitates negative selection of thymocytes and activation of T cells.